2012
DOI: 10.1126/scitranslmed.3004655
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Tonic Inhibition in Cerebellar Granule Cells Causes Motor Dysfunction in a Mouse Model of Angelman Syndrome

Abstract: Angelman syndrome is a neurodevelopmental disorder caused by loss of function of the UBE3A gene encoding a ubiquitin E3 ligase. Motor dysfunction is a characteristic feature of Angelman syndrome, but neither the mechanisms of action nor effective therapeutic strategies have yet been elucidated. We report that tonic inhibition is specifically decreased in cerebellar granule cells of Ube3a-deficient mice, a model of Angelman syndrome. As a mechanism underlying this decrease in tonic inhibition, we show that Ube3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 63 publications
5
111
0
Order By: Relevance
“…29). Tonic inhibition of granule cells in AS mice has been shown to be impaired, perhaps due to hyperfunctional GAT1-mediated reductions in available extrasynaptic GABA (37). To confirm these findings in our AS mice, we recorded both tonic and phasic inhibition in granule cells dialyzed with a high-chloride internal solution at -70 mV.…”
Section: Resultssupporting
confidence: 66%
“…29). Tonic inhibition of granule cells in AS mice has been shown to be impaired, perhaps due to hyperfunctional GAT1-mediated reductions in available extrasynaptic GABA (37). To confirm these findings in our AS mice, we recorded both tonic and phasic inhibition in granule cells dialyzed with a high-chloride internal solution at -70 mV.…”
Section: Resultssupporting
confidence: 66%
“…Recent studies have identified several neuronal proteins that are mis-regulated in AS neurons, including CAMKII, RhoA guanine nucleotide exchange factor 5 (EPHEXIN5), activity-regulated cytoskeleton-associated protein (ARC), GAT1, α1-NAKA, NAV1.6, and ANKYRIN-G (8)(9)(10)(11)(12). Some of these proteins are thought to be direct substrates of UBE3A.…”
mentioning
confidence: 99%
“…AS mice have significant neural circuit defects, suggesting that in the absence of Ube3a there is a disruption of excitatory/ inhibitory balance in the brain (6,10,12,13,(17)(18)(19). In addition, AS mice display defects in learning and memory, motor coordination, locomotor activity (14,17,20,21), and an increased number of seizures when exposed to an audiogenic challenge (6,11).…”
mentioning
confidence: 99%
“…Moreover, tonic inhibition is decreased in cerebellar granule cells while direct Ube3a target GAT1, a GABA transporter that removes GABA from the synaptic cleft, is increased in mouse cerebellar tissue, which could result in decreased GABA in the extrasynaptic space and ultimately contribute to cerebellar ataxia. [52] There is a significant decrease in inhibitory drive onto neocortical L2/L3 pyramidal neurons following the loss of excitatory inputs. [53] This overall excitatory/inhibitory imbalance could affect detection or integration of sensory information by decreasing the signal-to-noise ratio in certain areas of the brain.…”
Section: Targeted Therapeuticsmentioning
confidence: 99%